Dynamic PCBM:Dimer Population in Solar Cells under Light and Temperature Fluctuations. Issue 19 (27th March 2019) - Pont, Sebastian; Durrant, James R.; Cabral, João T.
Abstract: Photoinduced dimerization of phenyl‐C61‐butyric acid methyl ester (PCBM) has a significant impact on the stability of polymer:PCBM organic solar cells (OSCs). This reaction is reversible, as dimers can be thermally decomposed at sufficiently elevated temperatures and both photodimerization and decomposition are temperature dependent. In operando conditions of OSCs evidently involve exposure to both light and heat, following periodic diurnal and seasonal profiles. In this work, the kinetics of dimer formation and decomposition are examined and quantified as a function of temperature, light intensity, blend composition, and time. The activation energy for photodimerization is estimated to be 0.021(3) eV, considerably smaller than that for decomposition (0.96 eV). The findings are benchmarked with a variety of conjugated polymer matrices to propose a descriptive dynamic model of PCBM:dimer population in OSCs, and a framework is proposed to rationalize its interplay with morphology evolution and charge quenching. The model and parameters enable the prediction of the dynamic and long‐term PCBM:dimer populations, under variable temperature and light conditions, which impact the morphological stability of OSCs. Abstract : Schematic of the influence of light and thermal fluctuations on the PCBM:dimer population dynamics of a polymer:fullerene active layer. It is shown that a minimal rate model, parameterized by data from a facile UV–vis assay, can be employed to forecast the evolution and asymptotic behavior of this population, impacting the morphological and performance stability of solar cells.